2014
DOI: 10.1080/15320383.2014.907239
|View full text |Cite
|
Sign up to set email alerts
|

Metal Removal from Contaminated Soils Through Bioleaching with Oxidizing Bacteria and Rhamnolipid Biosurfactants

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…Metal ions can be removed from soil surfaces also by the biosurfactant micelles. The polar head groups of micelles can bind metals which mobilize the metals in water (Diaz et al 2015). The superior isolate BS37 showed the highest biosurfactant production and exhibited the greatest heavy metal removal efficiency which was identified according to the morphological and biochemical characterization of colony, and its antibiotic susceptibility were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Metal ions can be removed from soil surfaces also by the biosurfactant micelles. The polar head groups of micelles can bind metals which mobilize the metals in water (Diaz et al 2015). The superior isolate BS37 showed the highest biosurfactant production and exhibited the greatest heavy metal removal efficiency which was identified according to the morphological and biochemical characterization of colony, and its antibiotic susceptibility were tested.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, microorganisms in soil also have great effects on metal forms because of their ability to synthesize metabolites such as siderophores, bio-surfactants and organic acids [45]. Bacterial siderophores are able to bind metals and hence increasing metal bioavailability in the rhizosphere of plants [46], bio-surfactants produced by some microorganisms are capable of modifying the surface of various metals and favoring the metal separation from contaminated environments [47]. Moreover, Sheng et al [48] demonstrated the bio-surfactant-producing bacterial strain Bacillus sp.…”
Section: Total Metal In Mushroom and Metal Speciation In Soilmentioning
confidence: 99%
“…Unfortunately, the relatively high cost or the manner of production of biosurfactants still limits their widespread use. Although saponin (SAP) and rhamnolipids (RAM) are the two biosurfactants that have been tested most often, these substances have been tested separately with different soils or matrices. The efficiency of removal of metals from soil with biosurfactants such as these predominately depends on soil properties (e.g., soil texture, structure, clay content, cation exchange capacity, etc.).…”
Section: Introductionmentioning
confidence: 99%